2014
DOI: 10.1002/admi.201400184
|View full text |Cite
|
Sign up to set email alerts
|

In‐Situ Growth of Ultrathin Films of NiFe‐LDHs: Towards a Hierarchical Synthesis of Bamboo‐Like Carbon Nanotubes

Abstract: The synthesis of ultrathin films (UTFs) of NiFe‐LDHs has been achieved by means of an in situ hydrothermal approach, leading to a flat disposition of the LDH crystallites on the substrate, in clear contrast to the most common perpendicular orientation reported to date. Experimental factors like time of synthesis or the nature of the substrate, seem to play a crucial role during the growing process. The 2D morphology of the NiFe‐LDH crystallites was kept after a calcination procedure, leading to a topotactic tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 41 publications
3
39
0
Order By: Relevance
“…The common broadness of the peaks in the carbon sphere spectra indicates a low range in the structural order. 10,28 According to Bragg's equation, the interlayer spacing d 002 of our CS is 0.356 nm, which agrees with the literature, 30,31 with a low deviation for the ideal d 002 space (0.343 nm) in a graphitic structure (JCPDS-ICDD Card No. ).…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…The common broadness of the peaks in the carbon sphere spectra indicates a low range in the structural order. 10,28 According to Bragg's equation, the interlayer spacing d 002 of our CS is 0.356 nm, which agrees with the literature, 30,31 with a low deviation for the ideal d 002 space (0.343 nm) in a graphitic structure (JCPDS-ICDD Card No. ).…”
Section: Resultssupporting
confidence: 78%
“…26,28 Moreover, we have demonstrated that the calcinated NiFe-LDH preserves the structural integrity, with the in situ formed FeNi 3 nanoparticles being the main catalytic seeds. 27 Herein, control experiments consisting of the calcination of NiFe-LDHs at 900 1C, supplying H 2 but in the absence of a carbon source, gave rise to a mixture of NiFe 2 O 4 , NiO and FeNi 3 phases as revealed by XRPD (see SI 2.1, ESI †).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The processability of LDH into thin films is one of the most rapidly growing areas in this field, as the large-scale correct disposition of the LDH platelets would facilitate their application in energy storage and conversion devices. 20,37 Along this front, we checked the formation of continuous thin films by physical deposition. The first attempts with the water suspensions were unsatisfactory due to an inhomogeneous coverage even after using O 2 -plasma cleaning for the activation of the substrates (Fig.…”
Section: 23mentioning
confidence: 99%